PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP PERATAAN LABA (Studi Empiris Pada Perusahaan Yang Terdaftar Pada Indeks IDX30 Di Bursa Efek Indonesia Periode 2014-2018) - Huda, Syamsul; Suartini, Sri; Lestari, Indah Ayu (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
This study aims to identify and examine the effect of profitability (ROA) and leverage (DER) both partial and together on income smoothing companies listed on the index in the Indonesia Stock Exchange IDX30 2014-2018 period. The study population includes all companies listed on the index IDX30 in Indonesia Stock Exchange Period 2014-2018. Samples were determined by purposive sampling. Data analysis techniques in this research is descriptive verification. Hypothesis testing using multiple linear regression analysis model. The results showed that (1) profitability (ROA) have a significant effect on income smoothing. (2) leverage (DER) has no significant effect on income smoothing. (3) Profitability (ROA) and leverage (DER) jointly affect the income smoothing.